THE CORRELATION BETWEEN THE NUMBER OF VACCINES RECEIVED AND THE DEGREE OF SYMPTOMS COVID-19 PATIENTS IN THE EMERGENCY DEPARTMENT - Hilmia Maulina Hamida; Dody Setyawan (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2022)
Covid-19 patients who came to the emergency department in February 2022 are still relatively high with various degrees of symptoms from mild to severe. The condition of Covid-19 patients who came to the emergency department, some of them have already received the first dose of the vaccine to third dose (boster). However, there are also some of them have not been vaccinated at all. The purpose of this research is to know the correlation between the number of vaccines received and the degree of symptoms covid-19 patients in the emergency department. The method was quantitative research with retrospective design of cross sectional approach study. The data was taken from the Electronic Medical Record (RME) with a sample of patients who came to the emergency department in February 2022 with the age of more than 18 years old and positive antigen or PCR swab results. Research data collection was conducted in August 2022. The Research used RME to see the number of vaccines received by patients and the Guidelines of the Republic Indonesia Health’s Minister to determine the degree of symptoms Covid-19. The results showed that there was a correlation between the number of vaccines received and the degree of symptoms covid-19 patients (p value: 0,003 (<0,05)). Completeness the number of vaccine doses received can reduce the severity of Covid-19 symptoms, because it can increase immunity and provide a stronger immune response. Therefore, it is hoped that the public can follow the complete vaccination program suggested by the Government. Keywords: Degree of Symptoms Covid-19, Emergency Department, Number of Vaccines Doses